2023
DOI: 10.1371/journal.pone.0288158
|View full text |Cite
|
Sign up to set email alerts
|

SUNi mutagenesis: Scalable and uniform nicking for efficient generation of variant libraries

Abstract: Multiplexed assays of variant effects (MAVEs) have made possible the functional assessment of all possible mutations to genes and regulatory sequences. A core pillar of the approach is generation of variant libraries, but current methods are either difficult to scale or not uniform enough to enable MAVEs at the scale of gene families or beyond. We present an improved method called Scalable and Uniform Nicking (SUNi) mutagenesis that combines massive scalability with high uniformity to enable cost-effective MAV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In future work it will be important to extend the approach to longer domains and to full length proteins. Advances in DNA synthesis 40 , assembly 41 and mutagenesis 42,43 should facilitate this. In this study we have reported the effects of Domainome 1.0 variants on cellular protein abundance.…”
Section: Discussionmentioning
confidence: 99%
“…In future work it will be important to extend the approach to longer domains and to full length proteins. Advances in DNA synthesis 40 , assembly 41 and mutagenesis 42,43 should facilitate this. In this study we have reported the effects of Domainome 1.0 variants on cellular protein abundance.…”
Section: Discussionmentioning
confidence: 99%